Systems Thinking Interplay Between Project Complexities, Stakeholder Engagement, and Social Dynamics Roles in Influencing Construction Project Outcomes - Temitope Seun Omotayo; Jonathan Ross; Abiodun Oyetunji; Chika Udeaja (SAGE Open, 2024)
Construction projects are fraught with the challenges of cost overruns, schedule deviations, and not meeting expectations. Underlying these failures are factors related to complexity, stakeholder management, and external social dynamics. The literature review highlighted research gaps, leading to conceptualizing the research aim. The study explored the roles of project complexity, stakeholder engagement, and social dynamics in the UK construction project management sector. A survey research strategy combining qualitative interview questions was employed to extract data from project professionals across the UK. Convenience sampling resulted in a high response rate from seventy-three (73) participants across the UK. Four main themes emerged: project complexity and lessons learned; stakeholder engagement and social climate; project failures and conflicts; and project success. System thinking causal loop diagramming was applied in amalgamating implications drawn from the findings. The implications noted that challenges in governance, regulation, and legislation, coupled with stringent cost and schedule targets, added to project complexity, effective stakeholder engagement, clear communication, and understanding of social contexts were crucial for project success where complexities of stakeholders and social dynamics proved difficult.